2014
DOI: 10.11564/28-1-502
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socio-Demographic Factors on Risky-Sexual Behaviours of Adolescents in the North West Province of South Africa

Abstract: The present study sought Résumé La présente étude a cherché à combler un vide recherche sur les adolescents comportements à problème en Afrique du Sud par l'examen individuel et facteurs contextuels qui affectent sexuelle risque de comportements chez les noirs africains des adolescents dans une communauté pauvre de la Province du nord-ouest de l'Afrique du Sud. L'aide logistique et de régression Poisson techniques analytiques, Nous constatons que les individus et facteurs contextuels tels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…A study conducted in South Africa indicated that adolescents who report strong religiosity are less likely than their counterparts who report weak religiosity to report lifetime sex. The odds of adolescents who report strong religiosity were 54% less than those who report weak religiosity [11]. Several scholars have observed that adolescents who attached importance to religion were significantly more aware of the dangers of HIV/AIDS than their non-religious counterparts; they are more likely to delay sexual involvement than those with lower levels of religiosity [15].…”
Section: Literature Review Socio Demographic Factorsmentioning
confidence: 97%
See 3 more Smart Citations
“…A study conducted in South Africa indicated that adolescents who report strong religiosity are less likely than their counterparts who report weak religiosity to report lifetime sex. The odds of adolescents who report strong religiosity were 54% less than those who report weak religiosity [11]. Several scholars have observed that adolescents who attached importance to religion were significantly more aware of the dangers of HIV/AIDS than their non-religious counterparts; they are more likely to delay sexual involvement than those with lower levels of religiosity [15].…”
Section: Literature Review Socio Demographic Factorsmentioning
confidence: 97%
“…Age is another determining factor. In the same study, the timing of first sexual debut has found that the rate for older adolescents was about 27% higher than the rate for younger adolescents [11]. A study conducted in Finland and Estonia has observed a positive association between age and sexual experience, that is, as age increases the participation in sexual activity also increases [12].…”
Section: Literature Review Socio Demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Norviatin (2014) states that the status and frequency of dating in adolescents (Nursal, 2008) can influence the premarital sexual behavior in adolescents. Various researches show that the origin of school influences the risky sexual behavior in adolescents (Ryu,et al, 2007;Amoateng, Kalule, & Arkaah 2014;Mujayapura, 2014). Mujayapura's research showed that respondents from private schools (60%) had higher risk of sexual behavior than those from state school.…”
Section: Introductionmentioning
confidence: 99%